Chronic illness and sustainable careers: How individuals with multiple sclerosis negotiate work transitions in a middle-income country. (January 2020) - Vijayasingham, Lavanya; Jogulu, Uma; Allotey, Pascale
Abstract: Reports of work change and transitions are common amongst individuals with chronic illnesses such as multiple sclerosis (MS). However, there is little research on the lived experience of these work transitions. The scarcity of this research is particularly evident within low-and-middle-income countries, where protection laws and resources such as anti-discrimination laws and reasonable work modifications may not exist or be well enforced. In this paper, we explore how and why individuals with MS seek and achieve work transitions in the structural context of Malaysia. We interviewed ten working individuals with MS (July–december 2015) using a joint hermeneutic phenomenology and constructivist grounded theory approach. Using a broad conceptual lens of 'sustainable careers', we examine their careers as a series of experiences, decisions, and events, paying attention to the influences of context, time, their personal levels of agency and sense of meaning. Participants described work transitions as early as within the first year of diagnosis, that were prompted by voluntary, involuntary and semi-voluntary reasons. Key aspects of the process of seeking new roles included an exploration of alternative roles and paths, and then acquiring, trialing/adapting and remaining engaged in their new roles. Participants identified the perception and experience of 'being unemployable', based on how their diagnosis and short-term symptoms were responded to by employers. Nevertheless, participants used various strategies and career resources to obtain and maintain meaningful work roles. However, success in obtaining or maintaining new roles were not equally achieved. This research draws attention to the cumulative economic disadvantage of a chronic illness diagnosis, even at milder and episodic stages. Furthermore, it reiterates the need for cohesive structural protection in low-and-middle-income countries to facilitate a more equal ability to remain economically resilient and capable of engaging in meaningful long-term careers when living with a chronic illness. Highlights: Chronic illness even in an episodic phase, disrupts careers and prompts transitions. Offers careers scholarship as a way to study work course in illness populations. Probes the sequence of post-diagnosis career transitions in a LMIC setting. Sustainable careers are not equitably achieved by using career resources alone. Structural change is needed to support career sustainability in illness populations.